The Impact of Service Quality, Employee Competency, and Digitalization on Patient Satisfaction at X Clinic - Yoe, Patricia; Estella Bastiaan , Natasha; Edwin Wiyono, Alvin (Universitas Pelita Harapan, 2024)
This study aims to analyze the effect of service quality, employee competence, and digitalization on patient satisfaction in clinics. In the digital era, the integration of technology and the competence of healthcare personnel are critical to enhancing service quality and overall patient experiences. Using a quantitative approach, this study applies Structural Equation Modeling (SEM) with Partial Least Squares (PLS) and collects data through a Likert-scale questionnaire. A total of 100 clinic patients were selected as respondents using purposive sampling. The independent variables in this study are service quality, employee competence, and digitalization, while patient satisfaction is the dependent variable. Data was analyzed using SmartPLS to test construct validity, reliability, and inter-variable relationships. The results reveal that all three independent variables have a significant positive influence on patient satisfaction, with digitalization showing the strongest effect, followed by employee competence and service quality. The R-squared value of 0.623 indicates that 62.3% of the variance in patient satisfaction can be explained by the model. These findings suggest that clinics should prioritize digital transformation and continuous development of medical staff competencies, alongside maintaining service quality. The study contributes to the literature by confirming the importance of digital healthcare tools in improving patient satisfaction and providing a foundation for future research to explore additional variables and long-term impacts of digitalization in healthcare.